PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN DUKUNGAN SOSIAL KELUARGA PADA MINAT BERWIRAUSAHA SISWA SMK NEGERI 1 PAMEKASAN - Trisnawati, Novi (UNIVERSITAS NEGERI SURABAYA, 2014)
This study aims to analyze the influences of entrepreneurial knowledge and social family supports on students interest in entrepreneurship. Population of this study were students from grade XI, for academic year 2013-2014 with total 368 students. 191 samples were taken using simple random sampling. Data were collected by questionnaires and documentations. This study was using quantitative analysis with multiple linear regresion. The results showed that there are Partially, there is no effect of entrepreneurial knowledge on students interest in entrepreneurship, and where as there is effect of social family supports on students interest in entrepreneurship. Simultaneous effects betwen entrepreneurial knowledge and social family supports on students interest in entrepreneurship.